Toward Efficiency Limits of Crystalline Silicon Solar Cells: Recent Progress in High‐Efficiency Silicon Heterojunction Solar Cells. Issue 23 (10th April 2022) - Sun, Zhaoqing; Chen, Xiaoqing; He, Yongcai; Li, Jingjie; Wang, Jianqiang; Yan, Hui; Zhang, Yongzhe
Abstract: Photovoltaic (PV) technology is ready to become one of the main energy sources of, and contributers to, carbon neutrality by the mid‐21st century. In 2020, a total of 135 GW of PV modules were produced. Crystalline silicon solar cells dominate the world's PV market due to high power conversion efficiency, high stability, and low cost. Silicon heterojunction (SHJ) solar cells are one of the promising technologies for next‐generation crystalline silicon solar cells. Compared to the commercialized homojunction silicon solar cells, SHJ solar cells have higher power conversion efficiency, lower temperature coefficient, and lower manufacturing temperatures. Recently, several new record efficiencies have been achieved. To meet the continued demand for high‐efficiency solar cells, expectations for large‐scale mass production of SHJ solar cells are rising. To approach the efficiency limit and industrialization of SHJ solar cells, serious attempts have been made, yielding higher short‐circuit current, open‐circuit voltage, and fill factor. In this article, these recent advancements are reviewed, which reveals the future roadmap for approaching the efficiency limit. Abstract : From the authors' point of view, silicon heterojunction (SHJ) solar cells are the candidate technique that can best approach the efficiency limit. The engineering of the amorphous/crystalline silicon interfaces still needs to be emphasized for improving both the open‐circuit voltage and fill factor. To address the optical losses, the exploration of the ultimate design of SHJ solar cells should be carried through.